Modified Ghost Fluid Method with Axisymmetric Source Correction (MGFM/ASC) (Communications in Computational Physics, 2020)
In this work, we show that the modified ghost fluid method might sufferpressure mismatch at material interfaces and thus leads to inaccurate numerical results when directly applied to long term simulations of multi-medium flow problemswith an axisymmetric source term. We disclose the underlying reason and then develop a technique of linear distribution to take into account the effect of the axisymmetric source on the definition of ghost fluid states. In order to faithfully consider theeffect of the source term, the interfacial conditions related to derivatives are derivedand linear distributions of ghost fluid states are constructed based on a generalizedaxisymmetric multi-medium Riemann problem. Theoretical analysis and numericalresults show that the modified ghost fluid method with axisymmetric source correction (MGFM/ASC) can effectively eliminate the pressure error.
Keywords: Multi-medium compressible flow; axisymmetric flow; ghost fluid method; modified ghost fluid method; generalized multi-medium Riemann problem.